Social Rights and Economics : Claims to Health Care and Education in Developing Countries - Gauri, Varun (World Bank, Washington, DC, 2014)
The author analyzes contemporary rights-based and economic approaches to health care and education in developing countries. He assesses the foundations and uses of social rights in development, outlines an economic approach to improving health and education services, and then highlights the differences, similarities, and the hard questions that the economic critique poses for rights. The author argues that the policy consequences of rights overlap considerably with a modern economic approach. Both the rights-based and the economic approaches are skeptical that electoral politics and de facto market rules provide sufficient accountability for the effective and equitable provision of health and education services, and that further intrasectoral reforms in governance, particularly those that strengthen the hand of service recipients, are needed. There remain differences between the two approaches. Whether procedures for service delivery are ends in themselves, the degree of disaggregation at which outcomes should be assessed, the consequences of long-term deprivation, metrics used for making tradeoffs, and the behavioral distortions that result from subsidies are all areas where the approaches diverge. Even here, however, the differences are not irreconcilable, and advocates of the approaches need not regard each other as antagonists.